1998
DOI: 10.1063/1.476796
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer in benzoic acid crystals: Another look using quantum operator theory

Abstract: Articles you may be interested inNovel quantum mechanical/molecular mechanical method combined with the theory of energy representation: Free energy calculation for the Beckmann rearrangement promoted by proton transfers in the supercritical water Isotope effects associated with tunneling and double proton transfer in the hydrogen bonds of benzoic acid Double proton transfer in the complex of acetic acid with methanol: Theory versus experimentWe present a calculation of the rate of synchronous double proton tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Note that in this case, the oscillator that is symmetrically coupled, represented by the last term in Eqn (3), is in fact a physical oscillation of the environment. We were able to develop a theory [38] of reactions mathematically represented by the Hamiltonian in Eqn (3), and using this method and experimentally available parameters for the benzoic acid proton transfer potential, we were able to reproduce experimental kinetics as long as we included a symmetrically coupled vibration [39]. The results are shown in Table 1 below.…”
Section: A N E N Z Y M E a S A C O N D E N S E D P H A S E : T H E O mentioning
confidence: 99%
“…Note that in this case, the oscillator that is symmetrically coupled, represented by the last term in Eqn (3), is in fact a physical oscillation of the environment. We were able to develop a theory [38] of reactions mathematically represented by the Hamiltonian in Eqn (3), and using this method and experimentally available parameters for the benzoic acid proton transfer potential, we were able to reproduce experimental kinetics as long as we included a symmetrically coupled vibration [39]. The results are shown in Table 1 below.…”
Section: A N E N Z Y M E a S A C O N D E N S E D P H A S E : T H E O mentioning
confidence: 99%
“…They interchange by double proton transfer within the bridging hydrogen bonds of the dimer. The mechanism underlying the motion is dominated by phonon-assisted tunnelling and this is well established as the model system for translational molecular tunnelling [5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. We have made 99% 13 C substitution of the carboxycarbon which now acts as a Ôspy nucleusÕ monitoring the concerted motion of the two hydrogen atoms in the hydrogen bonds that bridge the BA dimer.…”
Section: Introductionmentioning
confidence: 98%
“…We realized that what was missing was a specific motion in the system that symmetrically moved the proton donor and acceptor closer to each other. Mathematically, we showed that a symmetric coupling to an environmental bath mode, rather than an antisymmetric coupling as in the Zwanzig picture characterized this motion 9 . The fact that this symmetric coupling gave essentially different physics was not a surprise – Marcus had discussed just such an effect in gas phase dynamics many years earlier 10 .…”
Section: A Brief Historymentioning
confidence: 87%